Use of cast immobilisation versus removable brace in adults with an ankle fracture: multicentre randomised controlled trial. (5th July 2021) - Kearney, Rebecca; McKeown, Rebecca; Parsons, Helen; Haque, Aminul; Parsons, Nick; Nwankwo, Henry; Mason, James; Underwood, Martin; Redmond, Anthony C; Brown, Jaclyn; Kefford, Siobhan; Costa, Matthew
Abstract: Objectives: To assess function, quality of life, resource use, and complications in adults treated with plaster cast immobilisation versus a removable brace for ankle fracture. Design: Multicentre randomised controlled trial. Setting: 20 trauma units in the UK National Health Service. Participants: 669 adults aged 18 years and older with an acute ankle fracture suitable for cast immobilisation: 334 were randomised to a plaster cast and 335 to a removable brace. Interventions: A below the knee cast was applied and ankle range of movement exercises started on cast removal. The removable brace was fitted, and ankle range of movement exercises were started immediately. Main outcome measures: Primary outcome was the Olerud Molander ankle score at 16 weeks, analysed by intention to treat. Secondary outcomes were Manchester-Oxford foot questionnaire, disability rating index, quality of life, and complications at 6, 10, and 16 weeks. Results: The mean age of participants was 46 years (SD 17 years) and 381 (57%) were women. 502 (75%) participants completed the study. No statistically significant difference was found in the Olerud Molander ankle score between the cast and removable brace groups at 16 weeks (favours brace: 1.8, 95% confidence interval −2.0 to 5.6). No clinically significant differences were found in the Olerud Molander ankle scores at other time points, in the secondary unadjusted, imputed, or per protocol analyses. Conclusions: Traditional plaster casting was not found to be superior to functional bracing in adults with an ankle fracture. No statistically difference was found in the Olerud Molander ankle score between the trial arms at 16 weeks. Trial registration: ISRCTN registry ISRCTN15537280 .